Chronic widespread back pain is distinct from chronic local back pain: evidence from quantitative sensory testing, pain drawings, and psychometrics - Gerhardt, Andreas; Eich, Wolfgang; Janke, Susanne; Leisner, Sabine; Treede, Rolf-Detlef; Tesarz, Jonas (The clinical journal of pain, 2016)
Whether chronic localized pain (CLP) and chronic widespread pain (CWP) have different mechanisms or to what extent they overlap in their pathophysiology is controversial. The study compared quantitative sensory testing profiles of nonspecific chronic back pain patients with CLP (n=48) and CWP (n=29) with and fibromyalgia syndrome (FMS) patients (n=90) and pain-free controls (n = 40). The quantitative sensory testing protocol of the “German-Research-Network-on-Neuropathic-Pain” was used to measure evoked pain on the painful area in the lower back and the pain-free hand (thermal and mechanical detection and pain thresholds, vibration threshold, pain sensitivity to sharp and blunt mechanical stimuli). Ongoing pain and psychometrics were captured with pain drawings and questionnaires. CLP patients did not differ from pain-free controls, except for lower pressure pain threshold (PPT) on the back. CWP and FMS patients showed lower heat pain threshold and higher wind-up ratio on the back and lower heat pain threshold and cold pain threshold on the hand. FMS showed lower PPT on back and hand, and higher comorbidity of anxiety and depression and more functional impairment than all other groups. Even after long duration CLP presents with a local hypersensitivity for PPT, suggesting a somatotopically specific sensitization of nociceptive processing. However, CWP patients show widespread ongoing pain and hyperalgesia for different stimuli that is generalized in space, suggesting the involvement of descending control systems, as also suggested for FMS patients. Because mechanisms in nonspecific chronic back pain with CLP and CWP differ, these patients should be distinguished in future research and allocated to different treatments.
Published online: September 8, 2015
Gesehen am 09.03.2018